Synthesis and analysis of data on inventories of medicinal plants in Madagascar - Rafidison, Verohanitra; Ratsimandresy, Fabien; Rakotondrafara, Andriamalala; Rakotondrajaona, Roland; Rasamison, Vincent Emile; Rakotoarisoa, Falitiana Marrino; Rakotonandrasana, Stéphan Richard (Ethnobotany Research and Applications, 2019)
Background: Madagascar, a big island in the Indian Ocean is one of the countries of hotspot biodiversity in the world. Among this biological richness, medicinal plants hold an important place in the everyday life of Malagasy people. However, the documentation on the uses of medicinal plants is still scarce and the synthesis of related works dated back to 1990. Methodes: This study was conducted by referring to 99 publications. The most cited taxa are determined according to the values of their frequency of citation. The fidelity level of species related to each disease is calculated using the formula of Friedmann et al. Results: The medicinal plants inventoried in Madagascar consist of 3245 species, of which 60% are endemic. Croton L. (98 species), Helichrysum Mill. (46 species) Noronhia Stadtm. ex Thouars, (39 species) et Psychotria L. (29 species) are the most represented genera. Albizia Durazz. (23,5%), Aloe A. Rich. (22,7 %) and Aphloia (DC.) Benn. (22,7%) are the most cited ones. The first three most diversified families are the same as those the mostly cited, namely Fabaceae (279 species), Asteraceae (238 species), and Rubiaceae (218 species). Psiadia altissima (DC.) Drake and Cinnamosma macrocarpa H. Perrier are the two first endemic autochthon species which are the most frequently cited. Harungana madagascariensis Lam. ex Poir. for the non endemic autochthon species and Lantana camara L. for the introduced species. The digestive and genito-urinary disorders, traumatic affections, poisoning and other consequences of external origins are the most predominant diseases treated with plants. The fidelity levels of the first five species used to treat these groups of diseases range between 50 and 95.5%. These diseases also belong to the most morbid ones in Madagascar. Conclusions: The present study highlight the actual state of Madagascan medicinal plants and the corresponding ailments. These data are useful to direct the future projects of biodiversity conservation in Madagascar and pharmacological and ethnobotanical investigations of medicinal plants. Key words: Madagascar, medicinal plants, actual state, most diversified and cited species